Case study of population of bagworm larvae (Pteroma pendula) and its relationship with rainfall / Adam Zulkarnaian Mustapa Kamal - Mustapa Kamal, Adam Zulkarnaian (Faculty of Plantation and Agrotechnology, 2017)
A study of population of bagworm larvae (Pteroma pendula) and its relation with rainfall was conducted at FGVP G. Besout 06, Sungkai, Perak, Malaysia. It aims to identify the density of pest, Pteroma pendula in selection blocks and to determine the relationship between the density of bagworm with rainfall. Methods of the case study are done by census the bagworm in a row of oil palm blocks. The collected data were recorded in the census form. Pteroma pendula is an ever-present pest in oil palm plantations and have short life cycle rather than others bagworm. Factors that can lead to the increasing number of its population are natural enemies, chemical control and relative humidity. Results showed that there was an infestation of bagworm with peak outbreak on April and May 2016 for the first instar larvae. Based on the correlation test result, there are negative weak correlation between bagworm and monthly rainfall thus conclude that there is no relationship between population of bagworm and monthly rainfall.